Children's Signaling of Their Uncertain Knowledge State: Prosody, Face, and Body Cues Come First. Issue 4 (2nd October 2019) - Hübscher, Iris; Vincze, Laura; Prieto, Pilar
ABSTRACT: Children achieve their first language milestones initially in gesture and prosody before they do so in speech. However, little is known about the potential precursor role of those features later in development when children start using more complex linguistic skills. In this study, we explore how children's ability to reflect on their degree of uncertainty develops. A total of 40 Catalan preschool children (and 10 adults) took part in a game in which they had to guess the identity of ten objects which they could touch but not see and then state how certain they were about each guess. An analysis of the children's reflections on their own uncertainty showed that (a) when preschoolers take a stance, they start to use multimodal uncertainty signals accurately before they are able to self-report their own level of (un)certainty; (b) they use epistemic prosodic and gestural markers before they start using lexical cues; and (c) multimodal cues signaling knowledge state become increasingly more complex over time. These findings suggest that preschoolers' expression of knowledge states through gestures and prosody reflects an early epistemic sensitivity which develops as they get older.